Law on Enforcement of Civil Judgments - The National Assembly (2008)
This Law prescribes principles, order and procedures for enforcement of civil judgments and rulings and fines, confiscation of assets, retrospective collection of illicitly earned money and assets, handling of material evidence and assets, court fees and civil rulings involved in criminal judgments and rulings, property parts of administrative judgments and rulings of courts, decisions on settlement of competition cases related to assets of judgment debtors by the Council for settlement of competition cases, and awards of commercial arbitrations (below colle ctively referred to as judgments and rulings); the system of civil judgment enforcement organizations and enforcers; rights and obligations of judgment creditors and judgment debtors, and persons with related interests and obligations; tasks and powers of agencies, organizations and individuals in civil judgment enforcement activities.